RANKL inhibition for giant cell lesions of the jaw: A retrospective cohort analysis. (November 2022) - Schreuder, Willem H.; Lipplaa, Astrid; Cleven, Arjen H.G.; van den Berg, Henk; Bisschop, Peter H.; de Jongh, Renate T.; Witjes, Max J.H.; Kessler, Peter A.W.H.; Merkx, Matthias A.W.; Edelenbos, Esther; Klop, Cornelis; Schreurs, Ruud; et al.
Abstract: Background: In all giant-cell-rich lesions (GCRL) occurring in bone, a common underlying excessive RANKL expression is held responsible for the osteolytic activity. Apart from giant cell tumour of bone (GCTB), systematic outcome analysis of RANKL inhibition in other GCRL is unavailable. The aim of this study is to assess the efficacy and safety of a 1-year denosumab protocol in giant cell lesions of the jaw (GCLJ). Methods: A retrospective cohort study was conducted compromising patients treated with a 1-year protocol of monthly subcutaneously administered 120 mg denosumab. Objective tumour response based on histology and imaging was used to calculate objective tumour response rate, progression-free survival (PFS) and time to progression. Type, severity and frequency of adverse events were recorded in a standardised way to assess safety. Results: Twenty patients, predominantly female (90%), were included. Fifty-five per cent of lesions were located in the mandible; most classified as aggressive lesions (90%). Thirty-five per cent (7/20) of cases were either recurrent after prior treatment or progressive, while on other drug treatment. Objective tumour response rate was 100% after 12 months of treatment. Median PFS was 50.4 months (95% CI 38.0–62.8) with a cumulative PFS rate of 22.6% (95% CI 1.8–43.4) at 5 years follow-up. Median time to progression was 38.4 months (95% CI 26.0–50.8). Treatment was well tolerated, and none of the patients had to interrupt therapy for toxicity. Conclusion: High-dose denosumab is effective and safe in achieving a complete response in GCLJ within 12 months. The high long-term relapse rate after treatment cessation is the main obstacle for denosumab to become standard treatment for GCLJ. Highlights: Giant cell lesions of the jaw respond effectively to one-year high-dose denosumab. After interruption of denosumab, the giant cell lesions of the jaw tend to recur. Similar outcomes to RANKL inhibition are seen among various giant-cell-rich lesions. For giant cell lesions of the jaw, denosumab is not considered standard treatment. Outcomes of different (dosing) strategies of denosumab still need to be awaited.